Using an incentive spirometer reduces pulmonary complications in patients with traumatic rib fractures: a randomized controlled trial - Shao-Kai Sum; Ya-Chuan Peng; Shun-Ying Yin; Pin-Fu Huang; Yao-Chang Wang; Tzu-Ping Chen; Heng-Hsin Tung; Chi-Hsiao Yeh (Trials, 2019)
Abstract Background An incentive spirometer (IS) is a mechanical device that promotes lung expansion. It is commonly used to prevent postoperative lung atelectasis and decrease pulmonary complications after cardiac, lung, or abdominal surgery. This study explored its effect on lung function and pulmonary complication rates in patients with rib fractures. Methods Between June 2014 and May 2017, 50 adult patients with traumatic rib fractures were prospectively investigated. Patients who were unconscious, had a history of chronic obstructive pulmonary disease or asthma, or an Injury Severity Score (ISS) ≥ 16 were excluded. Patients were randomly divided into a study group (n = 24), who underwent IS therapy, and a control group (n = 26). All patients received the same analgesic protocol. Chest X-rays and pulmonary function tests (PFTs) were performed on the 5th and 7th days after trauma. Results The groups were considered demographically homogeneous. The mean age was 55.2 years and 68% were male. Mean pretreatment ISSs and mean number of ribs fractured were not significantly different (8.23 vs. 8.08 and 4 vs. 4, respectively). Of 50 patients, 28 (56%) developed pulmonary complications, which were more prevalent in the control group (80.7% vs. 29.2%; p = 0.001). Altogether, 25 patients had delayed hemothorax, which was more prevalent in the control group (69.2% vs. 29.2%; p = 0.005). Two patients in the control group developed atelectasis, one patient developed pneumothorax, and five patients required thoracostomy. PFT results showed decreased forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1) in the control group. Comparing pre- and posttreatment FVC and FEV1, the study group had significantly greater improvements (p < 0.001). Conclusions In conclusion, the use of an IS reduced pulmonary complications and improved PFT results in patients with rib fractures. The IS is a cost-effective device for patients with rib fractures and its use has clinical benefits without harmful effects. Trial registration ClinicalTrials.gov, NCT04006587. Registered on 3 July 2019.